Perfil antropométrico de dos equipos universitarios de balonmano femenil - López García, Ricardo; Hernández Cruz, Germán; Rangel Colmenero, Blanca Rocío; López Walle, Jeanette M.; Ramos Carranza, Isela Guadalupe (ECORFAN, 2014)
An important aspect of working in sports nutrition is the weight change and body composition. Many athletes need to minimize body fat and weight to improve the biomechanics aspects or increase muscle mass to improve performance. For this reason, the aim of our study was to determine the anthropometric profile of handball players of two college teams. They we made 17 basic anthropometric measurements to both teams. Team 1 obtained a mesomorphic-endomorphic phenotype and Team 2 obtained an endomorphic-mesomorphic phenotype. The mesomorphic component is predominant in both teams; therefore, it can be assumed that the skeletal muscle strength in female handball is decisive.